(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The most important tasks in building software are managing software projects at the present time. Correct management, advance planning and identification of customer requirements and key functions of a software project. All this facilitates the recognition of the factor of time, money, human resources, capabilities and the possibility of finding quick solutions in the event of a problem during the production of the software project and thus achieving success for the project. The project manager is responsible for planning and identifying the critical points facing the project and finding alternatives in the event that a problem arises that may be in human resources, for example, the illness of a programmer, or the need for programmers who possess skills in a particular field, or the need to rely on special tools, etc., as he determines Software project manager the tasks assigned to the employees according to their own skills and experience to carry them out and also to determine how each task relates to another. In this paper, the squirrel algorithm is relied on in software project management.